One-Year Pilot Study Results of Newborn Screening for Spinal Muscular Atrophy in the Republic of Croatia - Darija Šimić; Ana Šarić; Ana Škaričić; Ivan Lehman; Branka Bunoza; Ivana Rako; Ksenija Fumić (MDPI AG, 2024)
Spinal muscular atrophy (SMA) is a neuromuscular and neurodegenerative disease caused by the homozygous deletion of SMN1 exon 7 in 95% of cases. The prognosis for SMA patients has improved with the development of disease-modifying therapies, all of which are available in Croatia. The best treatment outcomes occur when therapy is applied before symptoms appear, making newborn screening (NBS) for SMA a crucial factor. Since SMA NBS is the first genetic test performed in our laboratory, for successful implementation of the program, we had to overcome logistical and organizational issues. Herein, we present the results of the SMA NBS during the one-year pilot project in Croatia and verify the suitability of the Targeted qPCR™ SMA assay for SMA NBS. The pilot project started on 1 March 2023 in the Department for Laboratory Diagnostics of the University Hospital Center Zagreb. A total of 32,655 newborns were tested. Five SMA patients were detected, and their diagnoses were confirmed by the multiplex ligation-dependent probe amplification (MLPA) assay. There have been no false positive or false negative results, to our knowledge so far. The incidence of SMA determined during the pilot study is consistent with the SMA incidence data from other European countries.